Analisis Nilai Pendidikan Karakter Dalam Novel Lulus Karya RIPA AJP - Nuratia, Nuratia; Meliasanti, Ferina; Sutri, Sutri (Peneliti.net, 2024)
Literary works have various functions, one of which is an educational function. It is said to have an educational function because basically literature contains many positive values ​​that can be taken by readers and applied in everyday life. One form of literary work is the novel. The novel is a work of fiction with a long storyline, so that there are many conflicts from various characters in it. Pass by Ripa AJP. (3) Describe the results of the analysis in FatihZam's novel Aral on its use as teaching material in high school. This study uses BurhanNurgiyantoro's theory of intrinsic elements and Sri Narwanti's character education values. The data collection technique in this research is document study. The subject of this research is Ripa AJP's novel Lulus. The results of this study found intrinsic elements which include: (1) theme, (2) plot, (3) characters and characterizations, (4) setting, (5) point of view, (6) style of language, and (7) message. The values ​​of character education in the novel Lulus by Ripa AJP include: (1) honest, (2) curiosity, (3)responsibility, (4) friendly/communicative, and (5) love of the motherland.